Visualizing the invisible with the human body - Cale Johnson, J.; Stavru, Alessandro (Science, Technology, and Medicine in Ancient Cultures, 2020)
Physiognomy and ekphrasis are two of the most important modes of description in antiquity and represent the necessary precursors of scientific description. The primary way of divining the characteristics and fate of an individual, whether inborn or acquired, was to observe the patient's external characteristics and behaviour. This volume focuses initially on two types of descriptive literature in Mesopotamia: physiognomic omens and what we might call ekphrastic description. These modalities are traced through ancient India, Ugaritic and the Hebrew Bible, before arriving at the physiognomic features of famous historical figures such as Themistocles, Socrates or Augustus in the Graeco-Roman world, where physiognomic discussions become intertwined with typological analyses of human characters. The Arabic compendial culture absorbed and remade these different physiognomic and ekphrastic traditions, incorporating both Mesopotamian links between physiognomy and medicine and the interest in characterological 'types' that had emerged in the Hellenistic period.This volume offer the first wide-ranging picture of these modalities of description in antiquity.